2016
DOI: 10.1038/srep20765
|View full text |Cite
|
Sign up to set email alerts
|

Induction of virulence factors in Giardia duodenalis independent of host attachment

Abstract: Giardia duodenalis is responsible for the majority of parasitic gastroenteritis in humans worldwide. Host-parasite interaction models in vitro provide insights into disease and virulence and help us to understand pathogenesis. Using HT-29 intestinal epithelial cells (IEC) as a model we have demonstrated that initial sensitisation by host secretions reduces proclivity for trophozoite attachment, while inducing virulence factors. Host soluble factors triggered up-regulation of membrane and secreted proteins, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 68 publications
4
52
0
Order By: Relevance
“…Here instead, we chose to provide a detailed baseline from cultured Giardia trophozoites secreting proteins under a steady state in vitro . Nevertheless, our results are strongly supportive of a recent proteomic study looking at the effect of host attachment on the profile of Giardia -secreted proteins [15]. Prior to that study, several metabolic enzymes had been proposed to be released by Giardia trophozoites upon interaction with intestinal epithelial cells (IECs) [13], such as arginine deiminase (ADI), enolase, and ornithine carbamoyltransferase (OCT), which we were also able to identify from the culture supernatants of both assemblages.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Here instead, we chose to provide a detailed baseline from cultured Giardia trophozoites secreting proteins under a steady state in vitro . Nevertheless, our results are strongly supportive of a recent proteomic study looking at the effect of host attachment on the profile of Giardia -secreted proteins [15]. Prior to that study, several metabolic enzymes had been proposed to be released by Giardia trophozoites upon interaction with intestinal epithelial cells (IECs) [13], such as arginine deiminase (ADI), enolase, and ornithine carbamoyltransferase (OCT), which we were also able to identify from the culture supernatants of both assemblages.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, when GS was resequenced, GL50803_15564 was found to comprise 3 recently diverged orthologs (GSB_153537, GSB_155477, GSB_150353), and it may be that the positive selection pressure observed has been generated as a result of recent gene duplications in the assemblage B strain. GL50803_16779, an assemblage A (WB) GCATB, has previously been shown to be upregulated and involved in trophozoite motility in the early pathogenesis of Giardia [15]. In this study, this protein was found to be in WB’s top 5 secreted proteins (Table S4); its GS ortholog (GL50581_78) was also present but at a considerably lower level, suggesting that for this GCATB may play a more significant role in assemblage A than assemblage B.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Indeed, Giardia contains an impressive repertoire of immunoevasive products [36*] that are upregulated upon sensing secreted host factors even prior to parasite attachment [37] and could have implications for modulating host responses to co-pathogens or resident microbiota. For example, cathepsin B-producing Giardia strains are capable of cleaving IL-8 and attenuating neutrophil chemotaxis to inflammatory stimuli [38, 39].…”
Section: What Is the Pathway Between Giardia Infection And Poor Growth?mentioning
confidence: 99%